The Use of Local Waste in Traditional Compost Fertilizers - Fitri Anugrah Sari (Journal La Lifesci, 2021)
Elephant grass, dung, straw, and Gamal leaves, all of which are readily accessible in Makassar City, have not been extensively used by the local populace despite their abundance. These wastes may be processed into organic fertilizers that can be used to boost the economic worth of the trash by developing simple and suitable technologies. The material to be composted is mixed together with the promi, which is then composted. It takes just 6 weeks for the organic fertilizer to be entirely created, as seen by the final compost, which is odorless, dark brown, and water-insoluble, and contains N = 1.4 percent, P = 1.7 percent, and K = 1.8 percent, with a C/N ratio of 18.9 percent